Novel nanosynthesis of In2O3 and its application as a resistive gas sensor for sevoflurane anesthetic - Karmaoui, M.
A novel non-aqueous sol-gel route for synthesizing pure indium oxide (In2O3) nanoparticles (NPs) using indium acetylacetonate and n-butylamine as the reactive solvent, under solvothermal conditions, is herein proposed. The samples were characterized by an advanced X-ray method, whole powder pattern modeling (WPPM) and high-resolution transmission electron microscopy (HR-TEM), showing the exclusive presence of pure In2O3. Diffuse reflectance spectroscopy (DRS) was used to determine the optical band gap (E-g) of the sample. Moreover, these investigations also revealed that the In2O3 nanoparticles are quasi-spherical in shape, with a diameter of around 7 nm as prepared and 9.5 nm after thermal treatment at 250 degrees C. In2O3 NPs worked as highly sensitive sensing interfaces to provide resistance changes during exposure to sevoflurane, a volatile anesthetic agent used in surgical wards. The developed sensor demonstrated a good response and fast response/recovery time towards very low concentrations of sevoflurane in air, suggesting a very attractive application as a real-time monitoring analyzer in a hospital environment.